2003
DOI: 10.1111/j.1439-0523.2003.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of growth vigour and its association with other characters in chickpea

Abstract: Growth vigour plays an important role in the establishment of a normal crop. The F 2 population of a cross between high-and lowgrowth vigour varieties of chickpea segregated into 15 high : 1 low growth vigour. The results for recombinant inbred lines and BC 1 P 2 showed a good fit to the expected 3 : 1 ratio. The results indicated that growth vigour is controlled by two genes with duplicate dominant epistasis. No gene has so far been identified for growth vigour in chickpea. Correlation between growth vigour a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Similarly, in chickpea contradictory results have been reported (e.g. Sabaghpour et al, 2003;Toker and Canci, 2007;Gaur et al, 2008;Zaman-Allah et al, 2011b). Therefore, it can be concluded that optimal plant leaf area development depends on environment under consideration and its water availability pattern.…”
Section: Leaf Area Development Ratementioning
confidence: 97%
“…Similarly, in chickpea contradictory results have been reported (e.g. Sabaghpour et al, 2003;Toker and Canci, 2007;Gaur et al, 2008;Zaman-Allah et al, 2011b). Therefore, it can be concluded that optimal plant leaf area development depends on environment under consideration and its water availability pattern.…”
Section: Leaf Area Development Ratementioning
confidence: 97%
“…1994), rapid ground coverage (Siddique et al. 2001), early vigour (Sabaghpour et al. 2003), earliness and early maturity (Toker and Canci 2005) have been related to yield criteria under drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements of chickpea yields under DS have been achieved, mostly by breeding short duration cultivar that mature before the water deficit becomes too severe (Kumar et al 1985;Kumar and Rao 2001) with an often observed penalty in grain yield due to underutilisation of the available growing season. To overcome this self-imposed penalty, relatively longer (medium) duration chickpea cultivars have to be improved either though drought avoidance or tolerance mechanisms (Sabaghpour et al 2003).…”
Section: Introductionmentioning
confidence: 99%